Orchid diversity in disturbed forests of Terengganu and Kelantan, Malaysia, as inference for conservation - Besi, Edward Entalai (2018)
The uncontrolled logging in Peninsular Malaysia and the resulting mud floods in the lowland areas has been perilous, not to just human but also to other biodiversity, including the wild orchids. Their survival in these highly depleted areas has been minimally outweighed due to the inaccessibility and harsh environment. In relative to their uses commercially and their inclusion as one of the conservation objective, a detailed research on the diversity and ecology of orchids in the disturbed forest is crucial in strengthening the conservation framework. A botanical rescue missions within the Terengganu and Kelantan regions were done from November 2016 until May 2018, including study site selection, from existing logging sites in the Kenyir Lake area and disturbed secondary forests (DSFs) in the Kuala Koh and Tanah Merah areas. The herbarium specimens were processed and the living plants were rescued to ex-situ conservatory, and cultivated for further identification and phenological study. A total of 109 orchid species belonging to 39 genera was saved from their extremely disturbed habitats. The DSFs had a higher orchid density than the logging sites as the habitat conditions and energy productions were more reliable. However, the logged forests harboured higher diversity of orchids (H = 4.50 and D = 0.99) with 11 rare species were found along with four endemic species, and dominated by epiphytic orchids, which this was determined to be strongly influenced by the densities of fallen trees, durations of exposure to the dryness stress and unfavourable soil conditions. From this current study, 38 species are recorded as new records to Terengganu, four species are new records to Kelantan. A total of 280 orchid species from earlier collections from the disturbed forests of the Terengganu region are also listed in the checklist with a total of 86 species are new records to Terengganu, and one species is a new record to Malaysia; Dendrobium agamense; and another one species is a new record to Peninsular Malaysia; Crepidium oculatum. Foremost is the discovery of nine new species to science with five species are successfully described as Bromheadia petuangensis, Dendrobium ainiae, Dendrobium ruseae, Dendrobium mizanii, and Pinalia domii. This study also aimed to evaluate the resilience of wild orchids towards the environmental anthropogenic disturbances. The wild orchids employed two water-balance mechanisms in their reactions to the dryness-heat stress and water deficit in the disturbed forests; the 'drought avoidance' and 'drought escape' mechanisms. The wild orchids rescue mission to ex-situ conservatory was proven effective as all the rescued orchids were recovering well with 70.6% of them been recorded flowering or fruiting with an indication of a possibility of cross-pollination occurrence amongst them. Ten rare species were proposed under threatened categories according to IUCN Red List Categories and Criteria version 13 (March 2017). A conservation strategy was drafted for the orchids of disturbed forests with recommendations on the sustainable practices to avoid their local extinctions.